2022
DOI: 10.1101/2022.09.27.509700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adjusting for genetic confounders in transcriptome-wide association studies leads to reliable detection of causal genes

Abstract: Expression QTLs (eQTLs), provide valuable information on the functional effects of variants. Many methods have been developed to leverage eQTLs to nominate candidate genes of complex traits. These methods include colocalization analysis, transcriptome-wide association studies (TWAS) that correlate genetic components of expression with traits, and Mendelian Randomization (MR)-based methods. A fundamental problem of all these methods is that, when assessing the role of one gene in a trait using its eQTLs, nearby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Consistent with prior findings (79), we found that PT-WAS identified a greater number of genes associated with AD (n = 43) compared to colocalization (n = 6) at a genomewide significance threshold (p < 5 × 10 −8 , Supplementary Table 8). In contrast to the colocalized genes we identified, approximately 32% of the genes identified by PTWAS through rPCs (and 44% using averages) were located within 1 cM of APOE, which can likely be attributed partly to "LD hitchhiking" (80). LD hitchhiking can occur when some variants that are strong meQTLs for genes near APOE but are not risk variants for AD are in LD with AD risk variants near APOE that are not meQTLs for those nearby genes.…”
Section: Integration Of Meqtls and Ad Gwas Reveals Causal Relationshi...mentioning
confidence: 66%
“…Consistent with prior findings (79), we found that PT-WAS identified a greater number of genes associated with AD (n = 43) compared to colocalization (n = 6) at a genomewide significance threshold (p < 5 × 10 −8 , Supplementary Table 8). In contrast to the colocalized genes we identified, approximately 32% of the genes identified by PTWAS through rPCs (and 44% using averages) were located within 1 cM of APOE, which can likely be attributed partly to "LD hitchhiking" (80). LD hitchhiking can occur when some variants that are strong meQTLs for genes near APOE but are not risk variants for AD are in LD with AD risk variants near APOE that are not meQTLs for those nearby genes.…”
Section: Integration Of Meqtls and Ad Gwas Reveals Causal Relationshi...mentioning
confidence: 66%
“…Causal-PWAS is a novel extension of PWAS that directly adjust for genetic confounding 74 . PWAS in its original form suffers from confounding by LD; that is, purported cis-genetic effect may in fact be originated from nearby variants or genes, which independently affect a trait of interest.…”
Section: Causal-pwasmentioning
confidence: 99%
“…However, most identified associated variants lie in noncoding genome regions [1, 2], often obscuring their target genes and complicating the therapeutic target identification. Recent efforts to address this problem have resulted in the emergence of genome-scale molecular quantitative trait loci (QTL) annotations [3, 4] and the development of statistical methods bridging genetic variants with molecular phenotypes of gene candidates and complex traits [5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18]. These mechanism-aware putative causal gene (PCG) implication methods [8] focus on molecular phenotypes that can be unambiguously linked to specific genes.…”
Section: Introductionmentioning
confidence: 99%